Expeditious synthesis of carbon nanotubes by localized and high-frequency induction heating system for enhanced field emission characteristics - Jinho Choi; Hanna Lee; Amar Prasad Gupta; Jiwon Yoon; Jaekyu Jang; Jaeik Jung; Sung Ho Lee; Moonkyoo Kong; Jehwang Ryu (AIP Advances)
This study demonstrates rapid carbon nanotube (CNT) synthesis using a 150 kHz induction heating system, enabling precise temperature and pressure control in thermal chemical vapor deposition processes. CNT growth optimization at temperatures between 887 and 955 °C and pressures from 1 to 700 Torr reveals that an optimized temperature (887 °C) and pressure (100 Torr) yield enhanced field emission performance. The 150 kHz induction heating provided faster heating rates and a more consistent temperature distribution across the substrate, significantly enhancing growth efficiency. CNT grown using the induction heating system demonstrated high emission currents and outstanding stability during field emission tests. The induction heating approach reduces synthesis time, offering an efficient pathway for scalable production of field emission devices.